TINJAUAN TEBAL LAPIS PERKERASAN LENTUR DAN BANGUNAN PELENGKAP RUAS JALAN DESA LAYENI KABUPATEN MALUKU TENGAH - Alberth Latan; Elisabeth Talakua; Hendrie Tahya (Jurusan Teknik Sipil, 2023)
Road and Bridge Construction Engineering Study Program, Department of Civil Engineering, Ambon State Polytechnic. The Layeni Village Road Section of Central Maluku Regency is a secondary local cross road that has been damaged at several points on the road so that it must be upgraded from asphalt pavement to flexible pavement (Hotmix) and road complementary buildings. Based on the data analysis process obtained using the 2017 Bina Marga Method, the results for the Asphalt Concrete-Wearing Course (AC WC) layer thickness of 4 cm, for the Asphalt Concrete-Binder Course (AC BC) layer thickness of 6 cm, for the Asphalt Concrete-Base (AC BASE) layer thickness of 18 cm while the 1993 AASTHO Method obtained results for the Surface Course layer thickness of 15 cm, Base Course 10 cm and Sub Base Course 5 cm and for the existing drainage channel discharge obtained 0.31 m3 /second and the plan discharge is 0.98 m3 /second with a discharge difference of 67 m³ /s.